The population ecology of the Nile crocodile (Crocodylus niloticus) in the panhandle region of the Okavango Delta, Botswana - Bourquin, Sven Leon (Stellenbosch : Stellenbosch University, 2008)
Thesis (PhD (Conservation Ecology and Entomology))--Stellenbosch University, 2008.